Determination of Optimal Route for Newspaper Distribution Using Sweep Algorithm and Nearest Neighbour Method: Case Study - Anisa Agustina; Ayu Setiawati; Muhammad Iqbalnur; Virda Hersy Lutviana Saputri; Wahyudi Sutopo; Yuniaristanto (School of Industrial and System Engineering, Telkom University, 2022)
In general, the problem of production and distribution in the paper supply chain is the integration of plansto minimize total costs. Delivery times are required to be fast, sometimes not fulfilled due to problems inthe production and distribution process. One of the problems with newspaper companies in Surakarta is theslow distribution process due to the determination of the wrong distribution channel. This article aims tosolve the problem of determining the route of a newspaper company in the city of Surakarta by comparingtwo alternative choices, where the first alternative uses two fleets and the second alternative uses threefleets. This research uses the Sweep Algorithm and the Nearest Neighbor method in order to minimizetime and cost and to determine the best delivery path. From the results of data processing, it was found thatthe best proposal was the first alternative, namely by using two fleets because the distance traveled wasshorter with a difference of 0.45 km and resulted in savings of Rp. 467,940.00 every month.